Pain neuroscience education in persistent painful tendinopathies: A scoping review from the Tendon PNE Network - Escriche-Escuder, Adrián; Nijs, Jo; Silbernagel, Karin G.; Wilgen, C. Paul van; Plinsinga, Melanie L.; Casaña Granell, José; Cuesta-Vargas, Antonio (Elsevier, 2023)
Objective To conduct and report a scoping review of the available evidence of the effects and content of pain neuroscience education for patients with persistent painful tendinopathies. Methods PubMed, Embase, Web of Science, CINAHL, SPORTDiscus, and grey literature databases were searched from database inception to May 2022. Randomised and non-randomised controlled trials, non-controlled clinical trials, cohort studies, case series, case studies including people with persistent painful tendinopathy aged ≥18 years, a pain education intervention, and in English were included. Studies were excluded if they were cross-sectional studies, reviews, editorials, abstracts, or full-text not available or if included heterogeneous study cohorts, patients with tendon rupture, or patients with systemic diseases. Results five studies (n = 164) were included. Pain neuroscience education entailed face-to-face discussion sessions or educational materials including videos, brochures, paper drawings, and review questions. All studies used pain neuroscience education in conjunction with other interventions, obtaining significant benefits in outcomes related to pain, physical performance, or self-reported function, among others. Conclusions The application of pain neuroscience education in conjunction with other interventions seemed to improve several outcomes. However, considering the current knowledge about tendon pain and the scarcity of well-designed trials studying pain neuroscience education in tendinopathy, additional research is needed.
Keywords: Tendones - Enfermedades; Dolor; Neurociencias; Fisioterapia; Education; Pain; Physiotherapy; Tendinopathy; Educación de pacientes